PENGARUH REKRUTMEN, PELATIHAN DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA MERCURE BALI HARVESTLAND KUTA – BADUNG - Ni Made Dwi Puspitawati (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2020)
The use of quality human resources is needed in achieving hotel goals, one of which is improving employee performance. This study aims to analyze the effect of recruitment, training and compensation on employee performance at the Mercure Bali Harvestland Kuta-Badung. The sample size was 73 employees of Mercure Bali Harvestland Kuta-Badung. Determination of the sample using the saturated sampling method. Multiple linear regression analysis, multiple correlation analysis, determination analysis and t-test analysis were used to analyze this study. The results showed (1) recruitment had a positive and significant effect on employee performance, (2) training had a positive and significant effect on employee performance, (3) compensation had a positive and significant effect on employee performance. The implications of this research are expected by hotel managers to carry out recruitment well, provide training according to company needs, and be able to increase compensation so as to realize optimal employee performance.